2013
DOI: 10.1051/kmae/2013052
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of artificial neural networks and random forests to predict native fish species richness in Mediterranean rivers

Abstract: Key-words:Artificial neural networks, random forests, native fish, species richness, Mediterranean rivers Machine learning (ML) techniques have become important to support decision making in management and conservation of freshwater aquatic ecosystems. Given the large number of ML techniques and to improve the understanding of ML utility in ecology, it is necessary to perform comparative studies of these techniques as a preparatory analysis for future model applications. The objectives of this study were (i) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 83 publications
(101 reference statements)
1
29
0
1
Order By: Relevance
“…Moreover, the area under ROC curve (AUC) and the true skill statistic (TSS), which can also be considered independent of prevalence (Vaughan and Ormerod, 2005;Maggini et al, 2006), suggested good to excellent model performance (Pearce and Ferrier, 2000;Allouche et al, 2006). 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 19 fish abundance may provide valuable additional information (Fukuda et al, 2012;Olaya-Marín et al, 2013). Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the area under ROC curve (AUC) and the true skill statistic (TSS), which can also be considered independent of prevalence (Vaughan and Ormerod, 2005;Maggini et al, 2006), suggested good to excellent model performance (Pearce and Ferrier, 2000;Allouche et al, 2006). 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 19 fish abundance may provide valuable additional information (Fukuda et al, 2012;Olaya-Marín et al, 2013). Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, a review of the literature showed a relatively low number of ML applications in ecology compared with other scientific fields (Olden et al, 2008). Several studies have highlighted the urgent need for comparisons of the performance of different ML predictive techniques in ecology (Aertsen et al, 2011;Olaya-Mar ın et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This group of organisms is considered an effective indicator of aquatic ecosystem quality due to its sensitivity to anthropogenic disturbances (HELCOM, 2012;Smoli nski and Całkiewicz, 2015). Fish species richness and diversity are often used as a primary measures of ecological shifts and as a basis for planning protected areas (Knudby et al, 2010b;Olaya-Mar ın et al, 2013). Knowledge of the relationships between fish assemblages and environmental factors is important for effective conservation, and the application of novel statistical techniques can improve our understanding of these ecological processes (Olden et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it would be interesting to include other chemical and physical variables that were not available for this study (e.g. the percentage of a certain type of mesohabitat could be important to simulate fish species richness; Olaya‐Marin et al., ).…”
Section: Discussionmentioning
confidence: 99%